Potrzeba stymulacji a ekspozycja na zdarzenia traumatyczne - Dudek, Bohdan; Wojtecka, Katarzyna (Acta Universitatis Lodziensis. Folia Psychologica, 2009)
Problem. Prevalence of traumatic stress in general population is not so often but in some vocations it is a serious risk factor for employees’ health. A traumatic event is a main reason for PTSD and other mental disorders. There are multiple risk factors for PTSD development but the exposure to traumatic event is a main cause, included in a definition of PTSD. A need of stimulation, strongly connected to reactivity, may be treated as an individual resource because it let diminishing a chance of PTSD development but it may be treated as the risk factor of this disorder also. Hypothesis. Number of exposures to traumatic events is correlated to power of stimulation need. Subjects. 109 soldiers. Methods. Sensation Seeking Scale (SSS) by M. Zuckerman and Stressful Life Events Questionnaire (experimental version by M. Lis-Turlejska). Results. Relationships between results obtained in the particular dimension of the stimulation need and the number of traumatic events experienced by subjects are as follow: a dimension of thrill and adventure seeking (TAS) – rho = 0.30 (p < 0.008); an experience seeking dimension (ES) – rho = 0.20 (p < 0.060); a disinhibition dimension (DIS) – rho = 0.30 (p < 0.008) a boredom susceptibility dimension (BS) – rho = 0.20 (p < 0.060); a general dimension of stimulation seeking (G) – rho = 0.10 (p < 0.210). Rank correlation between a total results of SSS (a sum of subscales results) and the number of traumatic events experienced by the subjects is 0,25 (p < 0,008).